Principles of Orthopedic Practice for Primary Care Providers (Springer International Publishing, 2018)
Primary care providers (physicians, nurse practitioners, physician assistants) make decisions on a daily basis regarding treatments for musculoskeletal problems, including referrals to physical therapists, orthopedic surgeons and other specialists. Despite the large number of patients presenting with musculoskeletal complaints, primary care providers often feel poorly educated about how to assess and manage these patients This book provides a high yield and succinct resource on the assessment and management of these conditions. Written by expert orthopedic specialists at a major Harvard teaching hospital, this book fills that educational gap. Chapters overview specific body parts, typical presentations of disease, options for diagnostic testing, treatment paradigms, and anticipated outcomes of management both in the primary care setting and with a specialist. The text offers suggested pathways for working up and treating these problems with an emphasis on when referral to a specialist, or surgical intervention, is needed and when it is not. This is an ideal resource to educate primary care providers and empower them to engage in informed discussions with patients helping patients to arrive at treatment choices consonant with their preferences.